Testing of numerous hypotheses with the use of an optimal extended nonrandomized procedure - Koval, V. N.; Kuk, Yu. V.; Коваль, В. Н.; Кук, Ю. В.; Коваль, В. Н.; Кук, Ю. В. (Institute of Mathematics, NAS of Ukraine, 1997)
We propose a new procedure for testing hypotheses with the use of optimal statistical criteria.